Sulfate transport mutants affect hydrogen sulfide and sulfite production during alcoholic fermentation. Issue 6 (1st March 2021) - Walker, Michelle E.; Zhang, Jin; Sumby, Krista M.; Lee, Andrea; Houlès, Anne; Li, Sijing; Jiranek, Vladimir
Abstract: Hydrogen sulfide is a common wine fault, with a rotten‐egg odour, which is directly related to yeast metabolism in response to nitrogen and sulfur availability. In grape juice, sulfate is the most abundant inorganic sulfur compound, which is taken up by yeast through two high‐affinity sulfate transporters, Sul1p and Sul2p, and a low affinity transporter, Soa1p. Sulfate contributes to H2 S production under nitrogen limitation, by being reduced via the Sulfur Assimilation Pathway (SAP). Therefore, yeast strains with limited H2 S are highly desirable. We report on the use of toxic analogues of sulfate following ethyl methane sulfate treatment, to isolate six wine yeast mutants that produce no or reduced H2 S and SO2 during fermentation in synthetic and natural juice. Four amino acid substitutions (A99V, G380R, N588K and E856K) in Sul1p were found in all strains except D25‐1 which had heterozygous alleles. Two changes were also identified in Sul2p (L268S and A470T). The Sul1p (G380R) and Sul2p (A470T) mutations were chosen for further investigation as these residues are conserved amongst SLC26 membrane proteins (including sulfate permeases). The mutations were introduced into EC1118 using Crispr cas9 technology and shown to reduce accumulation of H2 S and do not result in increased SO2 production during fermentation of model medium (chemically defined grape juice) or Riesling juice. The Sul1p (G380R) and Sul2p (A470T) mutations are newly reported as causal mutations. Our findings contribute to knowledge of the genetic basis of H2 S production as well as the potential use of these strains for winemaking and in yeast breeding programmes. Abstract : The use of sulfate analogues and random mutagenesis to target sulfate transport and reduce hydrogen sulfide production in Saccharomyces cerevisiae . Abstract : Take Away S . cerevisiae wine strains were improved to limit hydrogen sulfide production. Sulfate analogues and random mutagenesis were used to target sulfate transport. Mutants affected hydrogen sulfide and sulfite production during fermentation. Crispr/Cas9 editing in EC1118 confirmed aetiology of phenotype. Sul1p (G380R) and Sul2p (A470T) mutations reduced hydrogen sulfide.